Pendampingan Penguatan Branding UMKM melalui Pelatihan Fotografi Produk untuk Komunitas Ibu PKK dan Fatayat NU Desa Temandang - Innarotul A’yun; Mohammad Ulil Abshor; Desi Kavita Sari (STAI Senori Tuban, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia have an important role in the economy, especially in developing the local economy. However, in increasingly fierce competition, many MSMEs have difficulty marketing their products effectively, especially through attractive product visualization. One of the main factors in increasing product competitiveness is strong branding, where product photography is a crucial element. Product photography training for MSMEs aims to improve their ability to utilize quality product photos as an effective marketing tool. In this context, this research conducted training for PKK and Fatayat NU members in Temandang Village, Tuban, the majority of whom are housewives involved in MSMEs. The method used is Participatory Action Research (PAR), focusing on active community participation in discussing challenges and formulating solutions. The training results show significant improvements in the quality of product photos, including lighting, composition, and editing, which allows products to better attract consumer attention on social media or the marketplace. This training also strengthens branding, increases marketing knowledge and skills, and encourages collaboration between participants to support each other and share experiences. It is hoped that this training can strengthen the competitiveness of MSMEs in the global market and contribute to local economic growth through increasing product sales.